A novel quinoxaline-based multifunctional probe: Sensitive and selective naked-eye detection of Fe3+ and fluorescent sensing of Cu2+ and its application - Seyedeh Roya Alizadeh; Pourya Biparva; Mohammad Ali Ebrahimzadeh (Arabian Journal of Chemistry, 2024)
A new quinoxaline derivative (QM: 6-methyl-2,3-di(quinoline-2-yl)quinoxaline) was synthesized as a colorimetric and fluorescent chemosensor for detecting Fe3+ and Cu2+ ions. QM can selectively detect Fe3+ among a number of essential cations and showed an obvious colorimetric response (colorless to yellow) in the presence of Fe3+ ions and considerable fluorescence quenching response towards Cu2+ ions. The molar ratio and Job plot showed a 1:1 stoichiometric ratio for the QM-Fe3+ and QM-Cu2+ complexes. The binding constants for QM-Fe3+ and QM-Cu2+ were found to be 3.335 × 105 and 2.230 × 103 M−1, respectively, using the Benesi-Hildebrand method. The quenching rate constant (Ksv) for QM-Cu2+ was 18.8 × 103 M−1 using the Stern-Volmer plot. The limits of detection and quantification for QM-Fe3+ were calculated as 0.236 and 0.787 µM, respectively, and those for QM-Cu2+ were 0.39 and 1.31 µM, respectively. Therefore, sensor QM can be used to quantify Fe3+ and Cu2+ ions in real samples with good recovery.